Corpora, translation, terminology… and beyond: objectives and perspectives - Maia, Belinda (Tradterm, 2021)
This paper will not describe any specific research in corpus linguistics. Instead, it will first reflect on the way many of us teaching languages and translation in university departments develop and use corpora in our research and teaching methodology. One of the objectives is to highlight the work by Professor Stella Tagnin and those of us with whom she has worked over twenty years, even if it does not bring anything new to the immediate area. It will go on to analyze how, apart from the didactic uses of these resources, and related research, their potential for Natural Language Processing (NLP) became increasingly important, and demonstrate how the methodology of corpus linguistics is now used in various disciplines, especially in interdisciplinary research. This analysis was prompted by involvement in a project to advise universities in two Central Asian countries on the creation of a masters’ degree in computational linguistics. The languages of these countries are very different from Western European languages, which obliged a re-assessment of my experience in linguistics and NLP in the context of English and Portuguese, when considering how the world’s less-resourced languages could join the mainstream of computational linguistics.